Hysteretic-Viscous Hybrid Damper System With Stopper Mechanism for Tall Buildings Under Earthquake Ground Motions of Extremely Large Amplitude - Hashizume, Shoki; Takewaki, Izuru (Frontiers in Built Environment, 2020)
This paper is aimed at proposing a hysteretic-viscous hybrid (HVH) damper system for tall buildings subjected to long-period pulse-type earthquake ground motions of extremely large amplitude. The HVH system was introduced for a single-degree-of-freedom (SDOF) system in the recent paper (Hashizume and Takewaki 2020). The HVH system consists of a large-stroke viscous damper and a hysteretic damper with a gap mechanism as a stopper for mitigating catastrophic damage. In the present paper, the effectiveness of the HVH system is shown for tall buildings. Pulse-type earthquake ground motions of extremely large amplitude were recorded in the past (for example Northridge 1994, Kumamoto 2016). These ground motions have a risk to cause catastrophic damage to high-rise and base-isolated buildings with long natural period. A double impulse is used here as a substitute of pulse-type ground motions of extremely large amplitude. Time-history response analyses are performed for an amplitude modulated critical double impulse to reveal the effectiveness of the proposed HVH system. In addition, the double impulse pushover (DIP) analysis, which was proposed by Akehashi and Takewaki (2019), is conducted for revealing the critical resonant performance of elastic-plastic tall buildings together with the analysis to a recorded ground motion at Kumamoto (2016). The comparison with the dual hysteretic damper (DHD) system composed of parallel-type small and large-amplitude hysteretic dampers is also conducted to investigate the seismic performance of the proposed HVH system.